Pengaruh Rasio Likuiditas Rasio Aktivitas Dan Profitabilitas Terhadap Return Saham Pada Perusahaan Makanan dan Minuman Yang Terdaftar Di Bursa Efek Indonesia (BEI) - Melly Nugrah Heni; Iskandar Iskandar; Ledy Setiawati (Jurnal Ilmu Akuntansi Mulawarman (JIAM), 2019)
This study aims to examine the liquidity ratio, activity ratio, and profitability of stock returns in food and beverage companies listed in food on the IDX. The number of research samples is 70 data from 10 companies studied. The study used an analytical tool with multiple linear regression tests, classical assumption determination tests and hypothesis testing namely t test and feasibility test model. The results of this study indicate that based on the test of the F Variabel curret ratio, Total Asset Turn Over and Return On Asset the three variables have a significant effect on stock returns in food and beverage companies listed on the indonesian stock exchange in 2011-2017. Based on the t test or partially the current ratio variable has a positive and significant influence on stock returns. Total Asset Turn Over variables have a positive and significant effect on stock returns. While Return On Asset variables that affects stock returns is the curret ratio.